2019
DOI: 10.1088/1361-6463/ab5c2a
|View full text |Cite
|
Sign up to set email alerts
|

Design of 3D broad-band and wide-angle absorber based on resistive metamaterial and magnetic absorbing material

Abstract: A 3D broad-band and wide-angle absorber (3D BWA) was designed through a 3D resistive metamaterial in which a traditional magnetic absorbing material was added on top of the metallic backplane. Owing to the better magnetic loss performance of the magnetic absorber at lower frequencies and superior impedance matching effect and ohmic loss property of the resistive films at higher frequencies, the absorption can be extended to a wider band through their combination. Simulation result shows that the absorption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…It can be observed that our absorber achieves a larger relative operating bandwidth with less magnetic material compared to all the competing pairs. For example, in [29], although the thickness is reduced by 1 mm compared to our study, the relative operating bandwidth is narrower, and a larger amount of magnetic material is used.…”
Section: Experimental Verificationmentioning
confidence: 71%
“…It can be observed that our absorber achieves a larger relative operating bandwidth with less magnetic material compared to all the competing pairs. For example, in [29], although the thickness is reduced by 1 mm compared to our study, the relative operating bandwidth is narrower, and a larger amount of magnetic material is used.…”
Section: Experimental Verificationmentioning
confidence: 71%
“…Among them, magnetic structural absorbers are the most studied. [14,15] However, dielectric structural absorbers attract increasing attention due to their unique advantages, such as a wider range of applicable material systems, which will help to expand the scope of application while reducing costs. [16] Meng et al proposed a dielectric absorber based on carbon black (CB) and BaTiO 3 (BT) nanoparticles embedded into polyvinylidene fluoride (PVDF) that were prepared using a simple blending and hot-moulding technique.…”
Section: Introductionmentioning
confidence: 99%
“…Some metal-dielectric-metal structure can show certain wide angle absorption for its strong resonance, but this is still not demand. To enhance the wide-angle absorption, a series of three-dimensional (3D) metamaterial structures [20][21][22][23][24][25][26] were therefore proposed, which aimed to achieve better performance. Some researchers using 3D metal/dielectric structure can obtain the wide-angle impedance match though, those results were limited to 60 • .…”
Section: Introductionmentioning
confidence: 99%